Análise da conformidade das informações contábeis na percepção do risco e tomada de decisão financeira do negócio - Thiel, Geruza Rodrigues (Universidade do Vale do Rio dos Sinos, 2017)
Accounting information is intended to support management decisions and the development of this information helps stakeholders to make better choices. In this sense, the study aimed to analyze how the conformity of accounting information affects the perception of risk and financial decision making of the business. It is a case study, descriptive and qualitative, carried out in a business environment of maritime services. The main results found that the fulfillment of the basic qualitative characteristics and improvement of the accounting information is part of the objectives of the sectors involved in the preparation of this information, however, there are two distinct perceptions in these departments regarding the current level of process capacity related to the support of information technology governance (GTI) to compliance. These are usual ways of providing accounting information to managers: reports, e-mails, periodic meetings (weekly, monthly and bimonthly), and the manager's own consultation with the system. Evidence has shown that there is no direct relationship between risk aversion of decision makers and the relative importance of accounting, this importance is tied to the perception of decision makers about the level of environmental risk and not necessarily about the risk aversion of each one. It is concluded that accounting information, by complying with its compliance and support of information technology governance, affects the risk preferences of decision makers since, together, accounting and GTI, they provide reference frameworks with greater visibility, agility, transparency and accessibility of the facts, allowing the clear decision of the manager. In this way, accounting information affect the perception of risk and financial decision making of the business by improving this perception and providing coherent and safer financial decisions, allowing the manager to take the risk or not, in a conscious way.
Keywords: Conformidade; Informações contábeis; Percepção do risco; Tomada de decisão; Compliance; Accounting information; Risk perception; Decision-making; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis